Effectiveness Of Hybrid/Blended Learning On Material Understanding In Practical Courses - Mellasanti Ayuwardani; Sri Eka Sadriatwati; Rara Ririn Budi Utaminingtyas; Rustono, Rustono (Cita konsultindo, 2023)
The development of technology that is entering the industrial era 5.0 plus the covid-19 pandemic which has turned into an ongoing covid-19 endemic, makes the use of technology very much needed. When the endemic announcement began, all face-to-face activities in the world of education gradually began to run, but with restrictions on activities and class capacity, including practicum lectures. The problem of this research is